2017
DOI: 10.1109/tits.2016.2598873
|View full text |Cite
|
Sign up to set email alerts
|

Safety in Vehicle Platooning: A Systematic Literature Review

Abstract: PostprintThis is the accepted version of a paper published in IEEE transactions on intelligent transportation systems (Print). This paper has been peer-reviewed but does not include the final publisher proofcorrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 37 publications
0
57
0
1
Order By: Relevance
“…Previous studies have shown that control transition requires a necessary amount of time that varies per driver and per moment (Merat et al 2014), and the level of awareness for the driver is also variable at the moment of control transition (Hjälmdahl, Krupenia, and Thorslund 2017). This poses questions in regard to safety at the point of the transition of control (Axelsson 2017), and also the design of the ADS to allow a driver this time while still maintaining an acceptable level of control. Further consideration can be given to the legislative aspect of where responsibility lies during a control transition and design conditions that may be set by the vehicle approval authority.…”
Section: Transition Of Control In Truck Platooningmentioning
confidence: 99%
“…Previous studies have shown that control transition requires a necessary amount of time that varies per driver and per moment (Merat et al 2014), and the level of awareness for the driver is also variable at the moment of control transition (Hjälmdahl, Krupenia, and Thorslund 2017). This poses questions in regard to safety at the point of the transition of control (Axelsson 2017), and also the design of the ADS to allow a driver this time while still maintaining an acceptable level of control. Further consideration can be given to the legislative aspect of where responsibility lies during a control transition and design conditions that may be set by the vehicle approval authority.…”
Section: Transition Of Control In Truck Platooningmentioning
confidence: 99%
“…Platooning, Intersections and Safety. Vehicles can opportunistically platoon to improve travel times, road usage, and safely do so [26]. Vehicle platooning on highways has been widely explored [27].…”
Section: A Vehicle-to-vehicle Cooperation and Reasoningmentioning
confidence: 99%
“…A specific concept that combines longitudinal and lateral automated driving is a platoon, a group of vehicles that drive closely together in a coordinated automated manner (Bergenhem et al, 2012;Ren & Green, 1994). Platooning of automated vehicles offers advantages compared to manual driving in terms of safety, road capacity, and fuel economy (e.g., Axelsson, 2017;Kunze et al, 2011;Larson, Liang, & Johansson, 2015).…”
Section: Emergence Of Automated Platooningmentioning
confidence: 99%